Video-triggered professional learning for general practice trainers: using the 'cauldron of practice' to explore teaching and learning. Issue 2 (3rd March 2020) - Clement, Tim; Howard, Duncan; Lyon, Eldon; Silverman, Jonathan; Molloy, Elizabeth
ABSTRACT: Many clinicians who take on a formal role of supervising or teaching trainees need to be taught how to teach and then continuously improve as educators. We describe the research-informed design of a novel professional development intervention that may be perceived by clinical educators as challenging, but being based on the key features of effective professional development is likely to lead to changes in their teaching practices. The video-club brings together a small group of clinical educators who have a shared interest in exploring their educator role and their teaching practices. It supports their learning through collective inquiry, using video-recordings of their authentic teaching practices as stimuli for discussion. A pilot has produced findings that are promising in terms of outcomes and impact. Participants responded to the educational design in the way that was envisioned and engaged with the requisite risk-taking and vulnerability that was necessary for their own learning and promoting learning for others.